Internalisasi Samma Ajiva Bagi Umat Buddha Sebagai Dasar Pertimbangan Mata Pencaharian Benar Pada Lingkungan Bisnis Travel 121 Express Di Kec. Tebas Kab. Sambas Kalimantan Barat - Then Se Fung; Irawati Irawati (STAB Maitreyawira, 2025)
This research is motivated by problems in internalizing Samma Ajiva for Buddhists as a basis for consideration of true livelihood in the 121 Express Travel Business Environment, Kec. Tebas Kab. Sambas Kalbar. The aim of this research is to find out the internalization of Samma Ajiva for Buddhists as a basis for consideration of true livelihood in the 121 Express Travel BusinessThis type of research is a qualitative descriptive method. Data collection was done by interview and observation. Interviews were conducted with the head of the Express Company, staff and passengers of 121 Express. The aim is to obtain more in-depth information about the internalization of Samma Ajiva for Buddhists as a basis for consideration of a decent living in the Travel 121 Express business environment. Observation is a data collection technique carried out by filling in the sheets provided.Based on the research conducted, it can be concluded that a) the characteristics of a profession that is appropriate and does not harm other parties is one that does not harm other parties in carrying out their work, a true profession has ethics and a code of ethics that has a sense of responsibility. b) results or profits are not the main thing to achieve, but rather consider the impact of the profession itself.